A strategic SWOT assessment of Vietnam’s halal market: Implications for Asian business and trade - Tuan, Lai Nam (Journal of Asian Business Strategy, 2025)
Vietnam has a significant opportunity to benefit from the growing global Halal economy, which can drive economic growth and enhance trade integration in Asia. This study uses SWOT analysis to examine Vietnam’s Halal landscape, highlighting strong institutional frameworks and strategic policies. The country’s solid agricultural foundation and rising Halal demand give it a competitive advantage. However, challenges such as regulatory inconsistencies, limited awareness of Halal standards among businesses, and complex supply chains hinder its full potential. A dual strategy is recommended: quickly entering the market while also improving long-term competitiveness through digital transformation and expanding agricultural exports. Policymakers should create a unified, internationally recognized Halal certification system to foster global trust. Businesses need to embrace digital technologies to optimize supply chains, expand market access, and enhance their brand presence both in Asia and worldwide. This research provides actionable insights for policymakers and businesses to tap into Vietnam’s Halal market potential, aligning with national economic goals and regional trade dynamics.